Next generation library catalogues – support for information literacy, Croatian case - Barbarić, Ana (Array, 2013)
The next-generation library catalogue sometimes referred to as the Library 2.0 catalogue or “the third generation catalogue” provides its intended audience with a more effective means for finding and using data and information. The next-generation catalogue should serve as an intuitive entry point for library users to discover library content. As the part of the libraries’ information literacy programs, the next-generation catalogue should be a tool designed to make it easier for citizens for find information, students to learn, teachers to instruct, and scholars to do research. Contemporary learning environments require students to have a variety of skills beyond those needed for being a successful student in the analog world. Information literacy standards, such as ACRL Information Literacy Standards for Higher Education deals, among other things, with evaluating information sources and addressing plagiarism and citation. Library resources, including online library catalogues, are considered trustworthy and credible. For that reason, OPAC tutorials should remain part of the libraries’ information literacy programs despite the convenience and online availability provided to users by other freely accessible web services. To remain prominent information literacy supporter, library catalogues need to bring new trends and old reliability closer together. Among the most prominent features of the next-generation catalog are a simple keyword search box (Google-like), enhanced browsing possibilities, spelling corrections, relevance ranking, faceted navigation, federated search, user contribution, and enriched content, just to mention a few. The purpose of this study is to determine which OPAC of the Croatian libraries offers more in terms of services and is more comparable to the next-generation library catalogue. The comparison will take place primarily in six areas: search, presentation of results, enriched content, user participation, personalization, and Web 2.0 technologies applied in Opals. Preliminary findings suggest that examined catalogues have implemented some features of the 2.0 catalogue. For example, catalogue of the Faculty of Humanities and Social Sciences Library, University of Zagreb, offers user comments and tags. It promotes user contributions by allowing sharing and/or recommending records on several social networks. This catalogue also offers relevance ranking to help users browse through the results quicker. Zagreb City Libraries OPAC shows similar features considering user-generated content. The plain bibliographic records, in this OPAC, are enriched with covers and annotations. Zagreb City Libraries also integrated into the catalogue lists of new, popular, and recommended titles. Crolist Union Catalogue offers relevance ranking but also clustering by type of the resource, author, language, publication year, subject, and availability. We can conclude that preliminary findings shows that new features are a great addition to the classical bibliographic data presented in library catalogues, but so far there are still many new possibilities which should be incorporated in the Croatian library catalogues.